Prediction of Cadmium Transfer From Soil to Potato in Karst Soils, China - Liu, Ke; Liu, Hongyan; Zhou, Xianyong; Chen, Zhu; Wang, Xulian (Frontiers in Environmental Science, 2021)
The contamination of food with the heavy metal Cd is a great concern around the world. In this study, a field survey was performed to investigate the characteristics of Cd transfer from soil to potato tubers (n=105). The results showed that the bioaccumulation factor of the potato tuber ranged from about 0.1 to 1, the soil threshold of Cd derived from the cumulative probability distribution was 0.15 mg·kg-1 in order to protect 95% of the potatoes through application of cumulative probability distribution method. Additionally, prediction models for Cd transfer were constructed based on the soil properties and the concentration of CaCl2 extractable soil Cd. The results of the analysis showed that pH was the critical factor affecting Cd uptake by potatoes. Additionally, the R2 of different empirical models increased from 0.354 to 0.715 with the increase of the soil parameters, and the predicted soil Cd concentration approached the measured values at values of about 0–15 mg·kg-1. The results of this study suggest that the probability distribution method was more strict than the empirical prediction models for estimating the ecological risk of the Cd contamination of potatoes in karst soils.